2017
DOI: 10.1007/s00122-017-2873-9
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of a major QTL qhir1 conferring maternal haploid induction ability in maize

Abstract: Key messageAmong the qhir11 and qhir12 sub-regions of a major QTL qhir1, only qhir11 has significant effect on maternal haploid induction, segregation distortion and kernel abortion.AbstractIn vivo haploid induction in maize can be triggered in high frequencies by pollination with special genetic stocks called haploid inducers. Several genetic studies with segregating populations from non-inducer x inducer crosses identified a major QTL, qhir1, on chromosome 1.04 contributing to in vivo haploid induction. A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 34 publications
3
27
0
1
Order By: Relevance
“…Ten ears were randomly selected from each entry in each replication. EnAR and EmAR were determined in each ear as described earlier ( Xu et al, 2013 ; Nair et al, 2017a ). For comparison of degree of EnAR and EmAR among the inducers with different levels of HIR (determined based on the lg testcrosses in AF16A), inducers were categorized into three classes, namely (a) inducers with low HIR (<5%), (b) inducers with moderate HIR (5–8%), and (c) inducers with high HIR (with >8% HIR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten ears were randomly selected from each entry in each replication. EnAR and EmAR were determined in each ear as described earlier ( Xu et al, 2013 ; Nair et al, 2017a ). For comparison of degree of EnAR and EmAR among the inducers with different levels of HIR (determined based on the lg testcrosses in AF16A), inducers were categorized into three classes, namely (a) inducers with low HIR (<5%), (b) inducers with moderate HIR (5–8%), and (c) inducers with high HIR (with >8% HIR).…”
Section: Methodsmentioning
confidence: 99%
“…Considering the time and resources involved in assessment of HIR, it would also be efficient to use any morphological traits known to be associated with high HIR to select plants or families that can lead to identification of inducers with high HIR. Recently it was shown that ears of individual plants and families with high HIR showed increased rates of endosperm and embryo abortion compared to plants or families with low or no HIR ( Prigge et al, 2012b ; Xu et al, 2013 ; Nair et al, 2017a ). It is also well known that haploid plants do occur in the progenies of inducers.…”
Section: Introductionmentioning
confidence: 99%
“…Out of two qhir1 sub-regions, the region containing qhir11 had a significant effect on the generation of maternal haploids independent of the qhir12 allele, whereas the “inducer” qhir12 allele did not cause haploid induction higher than the spontaneous rate observed in case of wild-type cobs. In addition, the region containing qhir11 was reported to display segregation distortion and kernel abortion, which are characteristic for haploidy inducer lines (Nair et al 2017 ).…”
Section: Generation Of Haploids Via Intraspecific Hybridizationmentioning
confidence: 99%
“…Quantitative trait loci (QTLs) are phenotypically defined genomic regions that contribute to allelic variation for a biological trait (Kumar et al ., ). Genes with a major effect can be experimentally mapped and characterized by establishing correlation between quantitative trait value and allelic states at linked genetic markers (Witzig et al ., ; Martin et al ., ; Nair et al ., ). Wondji et al .…”
Section: Introductionmentioning
confidence: 97%